2009
DOI: 10.1111/j.1365-2222.2009.03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐specific antibody and cytokine responses, mast cell reactivity and intestinal permeability upon oral challenge of sensitized and tolerized mice

Abstract: This work allows for the first time an appropriate comparison between sensitized and tolerized BALB/c mice towards OVA. It highlights important differences from other models of allergy, and thus questions some of the generally accepted notions of allergic reactions, such as the protective role of IFN-gamma, the importance of antigen-specific secretory IgA and the role of mucosal mast cells in intestinal anaphylaxis. In addition, it suggests that IL-17 might be an effector cytokine in food allergy. Finally, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 45 publications
5
60
2
3
Order By: Relevance
“…Although IgA is considered the first specific line of defense in protecting the intestine, it has been shown that the induction of tolerance in FA mice is associated with an inhibition of specific intestinal IgA [30]. The CC diet reduced total intestinal IgA protein and gene expression in agreement with previous studies [4,22], thus avoiding the synthesis of the specific IgA.…”
Section: Discussionmentioning
confidence: 56%
“…Although IgA is considered the first specific line of defense in protecting the intestine, it has been shown that the induction of tolerance in FA mice is associated with an inhibition of specific intestinal IgA [30]. The CC diet reduced total intestinal IgA protein and gene expression in agreement with previous studies [4,22], thus avoiding the synthesis of the specific IgA.…”
Section: Discussionmentioning
confidence: 56%
“…BALB/c mice orally immunized with OVA plus cholera toxin (CT) developed OVA-specific IgG1, IgG2a, and IgE antibodies (Supplemental Figure 1, A and B; supplemental material available online with this article; doi:10.1172/JCI43586DS1), as previously shown (14,15). Their splenocytes proliferated (Supplemental Figure 1C) and secreted significant amounts of IL-4, IL-13, and IFN-γ following in vitro stimulation with OVA (Supplemental Figure 1D), and their small intestine had increased infiltration with eosinophils and increased Il4, Il13, and Ifng mRNA expression, but no morphologic changes (Supplemental Figure 2, A-C).…”
Section: Resultsmentioning
confidence: 75%
“…However, functional studies provided evidence for the different roles of IL-17A and IL-17E in the regulation of immune responses: IL-17A is involved in inflammation, and IL-17E is able to induce T H 2 cytokine production and eosinophilia. Therefore, IL-17E but not IL-17A is associated with allergic sensitization [91][92][93][94].…”
Section: Non-celiac Gluten Sensitivitymentioning
confidence: 96%